Gestión de los servicios públicos y la satisfacción de los usuarios de la municipalidad distrital de Belén, 2020 - Macedo Mori, Patricia (2022)
The general objective of this research was to determine the relationship between the management of public services and the satisfaction of the users of the District Municipality of Belén, 2020, opting for a descriptive-correlational research and non-experimental design, for which it was I take a sample of 294 users of said entity, who were surveyed by means of a questionnaire of questions that analyzes their perception regarding the study variables; managing to conclude that, the management of public services in the District Municipality of Belén in the 2020 period is regular, since the municipality is not implementing social programs, likewise, a budget is rarely allocated for the improvement and maintenance of the streets, Fairs and campaigns are sometimes organized to encourage tourism. On the other hand, it was determined that user satisfaction is of a medium level, due to the fact that staff sometimes solve complaints and inconveniences, which causes the service provided to be seldom satisfactory, likewise, the municipality sometimes worries Due to the satisfaction of the users, the staff rarely provides personalized attention, since they are rarely trained, causing them not to provide clear and precise information. Finally, it was determined that there is a significant relationship between the management of public services and the satisfaction of the users of the District Municipality of Belén, with respect to the period 2020, with a significance at the 0.000 level and a Rho correlation coefficient of 0.820 which it is a considerable positive.